PENYULUHAN DAN PENGAPLIKASIAN EKO ENZIM DI KELURAHAN KEBUN SARI KOTA MATARAM - Wahyuni, Ida; Fathoni, Ahmad; Suwati, Suwati; Basirun, Basirun; Suriadi, Ahmad (Jurnal Agro Dedikasi Masyarakat (JADM), 2023)
Household waste is the main source of waste accumulation, both organic waste and inorganic waste. The size and lifestyle of each household can be used as a reflection of the amount of waste produced. Waste will increase if it is not processed and of course it will cause risks such as disease and strong odors. Until now, the waste problem has not been resolved properly, therefore, in this mentoring activity, outreach and application of one product from household organic waste, namely eco-enzyme, is carried out. The method of assistance is through counseling and practicing how to apply eco-enzymes so that people can utilize and apply eco-enzymes well. The results of mentoring activities show that the activity was welcomed enthusiastically by the community from the start of the activity to the end. Furthermore, after the extension activities, the implementing team succeeded in assisting the community to be able to apply good eco enzymes in this case to garden plants. The evaluation results showed an increase in knowledge of 75% and skills of 65%.